Unmet health care and health care utilization*. (28th January 2019) - Bataineh, Hana; Devlin, Rose Anne; Barham, Vicky
Abstract: The objective of this study is to examine the causal effect of health care utilization on unmet health care needs. An IV approach deals with the endogeneity between the use of health care services and unmet health care, using the presence of drug insurance and the number of physicians by health region as instruments. We employ three cycles of the Canadian Community Health Survey confidential master files (2003, 2005, and 2014). We find a robustly negative relationship between health care use and unmet health care needs. One more visit to a medical doctor on average decreases the probability of reporting unmet health care needs by 0.014 points. The effect is negative for the women‐only group whereas it is statistically insignificant for men; similarly, the effect is negative for urban dwellers but insignificant for rural ones. Health care use reduces the likelihood of reporting unmet health care. Policies that encourage the use of health care services, like increasing the coverage of public drug insurance and increasing after hours accessibility of physicians, can help reduce the likelihood of unmet health care.